Path of Survivors: An Analysis of Boy Erased and The Miseducation of Cameron Post - Trisha Zoe Tedjakarna (Institute of Research and Community Outreach - Petra Christian University, 2020)
This study aims to analyse the impacts of conversion therapy and the self-transformation of the main characters in Boy Erased and The Miseducation of Cameron Post, which are two films published post-legalisation of same-sex marriage in America. Both main characters showed signs of self-loathing, decreased authenticity, and feeling anger and disappointment due to conversion therapy. The two characters are first portrayed as victims and survivor of conversion therapy at the end of the film. Jared was shown as a silent victim turned outspoken survivor. Cameron was shown as a rebellious victim and survivor. Both films showed the growth from victims into survivors, which gave a strong, capable and hopeful image of homosexuals and is a contrast from some representation of homosexuals of the past. Despite the similarity in ending up as survivors, the two characters picked different fights. Keywords: Homosexual, Film, Victim, Survivor, Conversion therapy.